Penyesuaian Diri Caregiver Orang dengan Skizofrenia (Ods) - Rieska D. Ambarsari; Endah Puspita Sari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
This qualitative study aimed to find caregiver adjustment of people with schizophrenia post-treatment in the Mental Hospital and the factors that affect caregiver adjustment of people with schizophrenia. Respondents in this research study were two caregivers of people with schizophrenia. The first respondent was a member of the Schizophrenia Community Care of Indonesia, node Yogyakarta which has become a caregiver for nine years. The second respondent was caregiver people with schizophrenia whose domiciled in Magetan, East Java and has been becoming a caregiver for 10 years. The method used in data collection were interviews and observations. Analytical methods used were open coding, axial coding and selective coding. Based on survey result revealed that both of two respondents have the burden of personal and social as a caregiver people with schizophrenia. Several factors also affected the successful of caregiver people with schizophrenia in the process of positive self-adjusting. Internal factors that affected are the development of emotional maturity, intellectual and spiritual, physical and psychological state. External factors that affected are the environment, be it a family or community environmentKey words: Adjustment, Caregiver, Schizophrenia